Peningkatan Hasil Belajar dan Keaktifan Siswa pada Pembelajaran Tugasku Sehari-hari dengan Menggunakan Model Pembelajaran Make a Match di Kelas II SDN 2 Cingkrong - Susilowati, Susilowati (Universitas Sebelas Maret, 2020)
This research was conducted because of the low learning outcomes of grade II at SDN 2 Cingkrong.The method that researchers used in this classroom action research was the Make a Match cooperative learning model in which there were 4 stages, namely planning, action, observation and reflection. The subjects of this study were class II students of SDN 2 Cingkrong which consisted of 26 students. Data collection was carried out. Researchers through observation, interviews, tests and documentation. The results showed that 1) The application of the Make a Match type of cooperative model can increase the activity of teachers and students. On the results of observations of teacher activity in cycle I is 72.52, and increased to 90.32 in the cycle II. Meanwhile, the results of student activity observations in cycle I were 70.83, and increased to 91.7 in cycle II. 2) The increase in student learning outcomes can be seen from the average score of students in the Indonesian language subject at Pre PTK of 63.7 with a percentage of 46.15%, in the first cycle it became 72.7, with a percentage of 69.23%, and increased to 77. , with a percentage of 80.8% in cycle II. Mathematics also increased, namely at the beginning of the cycle of 64.1, with a percentage of 42.30%, in the first cycle it became 695 with a percentage of 57.7% and increased to 77, with a percentage of 80.76. In cycle II.